Cuadro de mando integral para el control de gestión en el hotel Mantahost de la ciudad de Manta - Loor Zambrano, Kelvin Cayetano (2019)
The main objective of this research was to develop a comprehensive dashboard for management control at the Mantahost hotel in Manta city, the descriptive method that represented the variables of the comprehensive dashboard, in relation to control aspects; and the inductive allowed to collect information about the main shortcomings of the hotel processes, which were the subject of study. In addition, the application of techniques contributed to the collection of field data, such is the case of the documentary review that provided solid information on the way the company keeps track of management and measures the performance of its employees. Ultimately the tools were applied for each dimension, questionnaires, process map, with their respective strategic objectives, indicators, goals and actions, as well as the Serviqual tool that expressed the level of customer satisfaction of the hotel, and finally the traffic light technique that allowed to visualize the degree of fulfillment of the established goals, and in this way facilitated decision-making.